2021
DOI: 10.5194/os-17-919-2021
|View full text |Cite
|
Sign up to set email alerts
|

Oil spill model uncertainty quantification using an atmospheric ensemble

Abstract: Abstract. We investigate the impact of atmospheric forcing uncertainties on the prediction of the dispersion of pollutants in the marine environment. Ensemble simulations consisting of 50 members were carried out using the ECMWF ensemble prediction system and the oil spill model MEDSLIK-II in the Aegean Sea. A deterministic control run using the unperturbed wind of the ECMWF high-resolution system served as reference for the oil spill prediction. We considered the oil spill rates and duration to be similar to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We acknowledge that uncertainties in the wind field are the main sources of variability in large and persistent oil slick scenarios (e.g. Li et al, 2019;Kampouris et al, 2021), but we have evidences that it is overridden by the ocean currents on short scales.…”
Section: Modeling Oil Drift Using Ensemble Forecastingmentioning
confidence: 88%
See 1 more Smart Citation
“…We acknowledge that uncertainties in the wind field are the main sources of variability in large and persistent oil slick scenarios (e.g. Li et al, 2019;Kampouris et al, 2021), but we have evidences that it is overridden by the ocean currents on short scales.…”
Section: Modeling Oil Drift Using Ensemble Forecastingmentioning
confidence: 88%
“…Less attention has been paid to the uncertainties in ocean models compared to wind forecasts due to its perceived secondary role in marine pollutant modelling (Li et al, 2019;Kampouris et al, 2021), though Jones et al (2016) showed that the oil slick drift modeling was improved when ocean current data retrieved from drogued buoys were included in the drift modelling. Additionally, other studies have also shown that poorly resolved mesoscale features (Jorda et al, 2007) and inertial oscillations (Brekke et al, 2021) impact the modeled drift of slicks, thus misrepresenting the predicted trajectory if not taken into account.…”
mentioning
confidence: 99%
“…14, 25 Low maternal tetraiodothyronine (T4) concentrations during gestation are associated with the impaired cognitive development of offspring as indicated by decreased Fagans or Bayleys Scores. 26 This study, therefore, is of public health importance and may provide valuable data that could be used in the formulation of reproductive health policies aimed at reducing the effects of neurotoxicants on infants. Data from this study showed significant changes in thyroid hormone concentrations, association with BPDE as a marker of PAHs during pregnancy and effects on the infants.…”
Section: Discussionmentioning
confidence: 99%
“…Locations 1 and 2 display a nonmonotonic change in the total sensitivity, with the wind coefficient having the largest influence. This outcome is unsurprising because the shear stresses imposed by the surface winds stretch the oil slick along the main wind direction, directly distorting its shape (Kampouris et al, 2021). However, the effects of the IFT and viscosity are generally not negligible, as observed from the results for Locations 1 and 2.…”
Section: Spill Motion and Deformationmentioning
confidence: 94%